1976
DOI: 10.1080/03014467600001251
|View full text |Cite
|
Sign up to set email alerts
|

Maximum aerobic power and physical dimensions of children

Abstract: Age, height, mass, fat-free mass and vital capacity were used as predictors of maximum aerobic power (VO2 max). The variables were cast in linear form by logarithmic transfomation and submitted to multiple regression analysis. Results indicate VO2 max as a power function of age, height and mass in 50 untrained boys aged 7 to 13 years. In this group the relationship between VO2 max and body mass may be expressed by the equation Y=0.076X0.88 (r=0.92, P <0.01). Age, height and mass together accounted for 89 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In trained children, it seemed as if maximal aerobic power was almost a linear function of mass with an exponent close to 1.0. In contrast, maximal aerobic power in untrained children was closer to body weight raised to the power of 0.88 (McMiken, 1976). These data would tend to support the idea that in normally growing children with no unusual participation in physical activities body mass increases at a slightly faster rate than maximal aerobic power.…”
Section: Dimensional Analysis Of Maximal Aerobic Powermentioning
confidence: 63%
See 1 more Smart Citation
“…In trained children, it seemed as if maximal aerobic power was almost a linear function of mass with an exponent close to 1.0. In contrast, maximal aerobic power in untrained children was closer to body weight raised to the power of 0.88 (McMiken, 1976). These data would tend to support the idea that in normally growing children with no unusual participation in physical activities body mass increases at a slightly faster rate than maximal aerobic power.…”
Section: Dimensional Analysis Of Maximal Aerobic Powermentioning
confidence: 63%
“…However, McMiken suggests that adolescents undergoing aerobic training increase their maximal aerobic power linearly with their body mass. McMiken (1976) also concluded that models relating maximal aerobic power to age, height or vital capacity are not very useful.…”
Section: Dimensional Analysis Of Maximal Aerobic Powermentioning
confidence: 99%
“…6 However, measurements of VO 2 MAX in 6-7 year old children are sparse, and representative data do not exist. [6][7][8][9][10][11] Even in older children and adolescents, very few population based studies exist. 10 12 13 The reasons for this include difficulties in testing young children.…”
mentioning
confidence: 99%
“…Several studies have compared the physical characteristics of elite junior performers in different sports with those of non-elite competitors and non-athletic children (McMiken 1975;Buckler & Brodie 1977;Bloomfield et al 1990). Several studies have compared the physical characteristics of elite junior performers in different sports with those of non-elite competitors and non-athletic children (McMiken 1975;Buckler & Brodie 1977;Bloomfield et al 1990).…”
Section: The Elite Young Athletementioning
confidence: 99%